Lessons learned on teaching a global audience with massive open online courses (MOOCs) on health impacts of climate change: a commentary - Barteit, Sandra; Sié, Ali; Yé, Maurice; Depoux, Anneliese; Louis, Valérie R.; Sauerborn, Rainer (Globalization and health, 2019)
The adverse health impacts of climate change are increasing on a global level. However, knowledge about climate change and health is still unavailable to many global citizens, in particular on adaptation measures and co-benefits of health mitigation. Educational technologies, such as massive open online courses (MOOCs), may have a high potential for providing access to information about climate change links to health for a global audience.